Protest camps: an emerging field of social movement research. Issue 3 (29th November 2013) - Frenzel, Fabian; Feigenbaum, Anna; McCurdy, Patrick
Abstract Recently protest camps have emerged around the world as a highly visible form of protest. Part and parcel of new social movement activism for over 40 years, they are important sites and catalysts for identity creation, expression, political contention and incubators for social change. While research has punctually addressed individual camps, there is lack of comparative and comprehensive research that links historic and contemporary protest camps as a unique area of interdisciplinary study. Research on the phenomenon to date has remained punctual and case based. This paper proposes to study protest camps as a distinct new field of research in social movement studies. Existing literature is critically reviewed and framed in three thematic clusters of spatiality, affect and autonomy. On the basis of this review the paper develops a research approach based on the analysis of infrastructures used to make protest camps. We contest that an infrastructural analysis highlights protest camps as a unique organizational form and transcends the limits of case‐based research while respecting the varying contexts and trajectories of protest camps.